School Psychology Manpower Characteristics and Needs in Rural and Urban Tennessee: A Five Year Follow-up - Jon E. DeVore; Thomas K. Fagan (Journal of Research in Rural Education, 1983)
A five-year followup survey was conducted with both rural and urban Tennessee school administrators to ascertain current school psychology manpower characteristics and needs and to determine how these parameters have changed over that period of time. Psychological services continue to be reported as available in almost all districts reporting, and increases are reported in the number of full-time personnel providing service, in the number of personnel holding State Department of Education certification as a school psychologist, and in the level of desired training of psychological personnel. A substantial number of administrators continue to indicate the quantity of psychological services is inadequate to meet their needs, but the number of actual position openings has declined over the five year period and are very few in number in relation to reported needs. The possible implications of the data to overall manpower concerns, and specifically to the Master Teacher-Better Schools programs, are discussed.